2016
DOI: 10.1097/inf.0000000000001081
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Complications in Former Bacillus Calmette-GuÉrin Osteitis Patients

Abstract: In 160 Finnish former Bacillus Calmette-Guérin osteitis patients, a questionnaire revealed that later in life, 22 (13.8%) had mild orthopedic complications as a consequence of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Partial dominant IFN‐γR1 deficiency, which belongs to the MSMD, was found in three of six Japanese children with BCG osteitis . All Japanese cases were curable with surgery and antimicrobial treatment, in line with the present cases …”
Section: Discussionsupporting
confidence: 88%
“…Partial dominant IFN‐γR1 deficiency, which belongs to the MSMD, was found in three of six Japanese children with BCG osteitis . All Japanese cases were curable with surgery and antimicrobial treatment, in line with the present cases …”
Section: Discussionsupporting
confidence: 88%
“…Moreover, patients with confirmed or suspected immunodeficiency could be prone to subsequent atypical infections in the previous BCG osteitis site and also present with multiple lesions 13. A recent study evaluating 160 former Finnish patients diagnosed 19–47 years ago in infancy reported a higher rate of 13.8% to have orthopedic complications, such as leg length discrepancy and chronic pain in the affected limb 14. Therefore, surveillance for serious adverse reactions following BCG vaccination and monitoring their long-term outcomes would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the study from Thailand reported, in addition to five localised BCG osteitis cases, also three cases with disseminated BCG infection, and two of them had severe combined immunodeficiency and one had Wiskott-Aldrich syndrome. 8 Thus, the systematic review, 2 and the basic and outcome data of the 222 Finnish BCG osteitis patients 3,4,21,25 and the data of the 93 new patients included in the present review [5][6][7][8][9][10] confirm that there are no major immunological problems in the BCG osteitis patients, if the infection is not disseminated, and if multiple or recurrent lesions are not present.…”
Section: Immunologymentioning
confidence: 80%
“…We carried out a posted questionnaire study for those 207 Finnish BCG osteitis patients with address data available when they were 21-49 years old, and 160(72.1%) of them answered. 22,25 Twenty-two (13.8%) reported orthopaedic sequelae which they connected to BCG osteitis in infancy. Most complications were mild and had not needed any treatment, but five (3.1%) reported that surgery was required.…”
Section: Ther Apymentioning
confidence: 99%